2014
DOI: 10.1038/srep05665
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium yoelii Vitamin B5 Pantothenate Transporter Candidate is Essential for Parasite Transmission to the Mosquito

Abstract: In nearly all non-photosynthetic cells, pantothenate (vitamin B5) transport and utilization are prerequisites for the synthesis of the universal essential cofactor Coenzyme A (CoA). Early studies showed that human malaria parasites rely on the uptake of pantothenate across the parasite plasma membrane for survival within erythrocytes. Recently, a P. falciparum candidate pantothenate transporter (PAT) was characterized by functional complementation in yeast. These studies revealed that PfPAT mediated survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 24 publications
3
58
0
Order By: Relevance
“…The same targeting vector was used to disrupt the dispensable PyP230p locus as a control for the transfection vector and procedures. All vectors were linearized and transfected in the same transfection experiment with PyPAT , which was previously published 22 . Transgenic parasites were cloned and analyzed by PCR to confirm the genetic replacement events and the deletion of PyPanK1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same targeting vector was used to disrupt the dispensable PyP230p locus as a control for the transfection vector and procedures. All vectors were linearized and transfected in the same transfection experiment with PyPAT , which was previously published 22 . Transgenic parasites were cloned and analyzed by PCR to confirm the genetic replacement events and the deletion of PyPanK1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in P. lophurae have shown that this avian parasite can scavenge host CoA for survival in ducks erythrocytes 6 21 . Similarly, genetic studies in the murine malaria parasite P. yoelii have shown that parasites lacking a candidate pantothenic acid transporter undergo normal asexual development in mouse erythrocytes, suggesting the presence of an alternative route for CoA biosynthesis in this parasite or an alternative pantothenate secondary transporter 22 .…”
mentioning
confidence: 99%
“…Although a triose phosphate shuttle has been identified as a second source of reducing equivalents in the T. gondii apicoplast [117], there is no evidence for such a pathway in Plasmodium [21,26,112,185], leaving the balance of reducing power in the parasite organelle in apparent deficit. The source of the biotin, thiamine pyrophosphate and CoA required by ACC, PDH and ACPS are also somewhat unclear, with enzymes involved in the synthesis or scavenging of these cofactors identified in Plasmodium [26,187,188], but little research to date addressing their provision to the apicoplast [189][190][191][192][193]. To gain a more wholistic understanding of FASII, characterization of its remaining enzymes and elucidation of these underlying pathways is a necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion mutants in P. berghei and P. yoelii have shown no effect on the parasite life cycle and in fact the P230p locus has even been used as a reporter insertion site (Janse et al, 2006; van Dijk et al, 2010; Lin et al, 2011; Hart et al, 2014). Functional redundancy with Pfs230 has been ruled out since the expression pattern of these proteins is different and no compensating upregulation was observed for Pfs230p in a ΔPfs230 mutant (Eksi and Williamson, 2002; Eksi et al, 2006).…”
Section: -Cys Proteins In the Sexual Stagesmentioning
confidence: 99%